2005
DOI: 10.1007/11513988_45
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Algorithms for Inter-procedural Analysis of Safety Properties

Abstract: Abstract. Automaton-based static program analysis has proved to be an effective tool for bug finding. Current tools generally re-analyze a program from scratch in response to a change in the code, which can result in much duplicated effort. We present an inter-procedural algorithm that analyzes incrementally in response to program changes and present experiments for a null-pointer dereference analysis. It shows a substantial speed-up over re-analysis from scratch, with a manageable amount of disk space used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…2. The tool uses the goto-cc compiler provided by the CProver framework 4 . The goto-cc compiler produces an input model of the source code of C program (called goto-binary) suitable for automated analysis.…”
Section: Tool Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…2. The tool uses the goto-cc compiler provided by the CProver framework 4 . The goto-cc compiler produces an input model of the source code of C program (called goto-binary) suitable for automated analysis.…”
Section: Tool Architecturementioning
confidence: 99%
“…Either, the models constituted an entire reachable abstract state space [9,4] that was revalidated after a change. Alternatively, behavioral models of different components of the software [3] were constructed (by employing techniques for learning regular languages) and then substitutability between the original and the altered components was analyzed after each change.…”
Section: Related Workmentioning
confidence: 99%
“…Pollock and Soffa [24] presented a precise incremental iterative algorithm using change classification and reinitialization for bitvector problems. In [10], an algorithm is presented that incrementally analyzes the verification of safety properties of a program. In [33], an incremental algorithm is presented which analyzes part of the program assuming no previous analysis result.…”
Section: Related Workmentioning
confidence: 99%
“…[23] observed that large libraries change less frequently than the applications that use them, so the libraries can be pre-analyzed for speeding up verification of the applications. Conway et al [6] observed that programs are usually modified in small incremental steps. So, after the application was verified once, only the modified functions and functions that transitively call them have to be re-verified.…”
Section: Background and Related Workmentioning
confidence: 99%